THE ROLE OF THE FACULTY OF COMMERCE AND ECONOMICS IN LIBYA'S DEVELOPMENT - El Oreibi, Dean (Dirasat in Economics and Business, 1966)
THE ROLE OF THE FACULTY OF COMMERCE AND ECONOMICS IN LIBYA'S DEVELOPMENT